DETERMINAN PERTUMBUHAN LABA PADA PERUSAHAAN SUBSEKTOR PERTANIAN - Ajijah Harahap; Budi Gautama Siregar; Ali Hardana (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
The existence of Islamic banks regarding the products and services offered is still poorly known and understood by the people of Aek Tampang Village, South Padangsidimpuan District and some consider that Islamic banks are the same as conventional banks. This study aims to analyze the effect of marketing strategy and knowledge on the decision to become a customer. The population of this research is the Aek Tampang community, South Padangsidimpuan District. By using the Slovin formula, so the number of samples is 99 people. Data was collected by means of interviews and distributing questionnaires. Data analysis was carried out with the help of the SPSS version 23 application. The results of this study found that marketing strategy had no effect on the decision to become a customer of a sharia bank and knowledge had an influence on the decision to become a customer.